GE_GERICHTE P/21721/2016 vom 27. April 2018 - GE Cour de justice (2018)
DOMMAGE MATÉRIEL ; FIXATION DE LA PEINE ; EXPULSION(DROIT PÉNAL) | CP.186 CP; CP.139.al1; CP.144.al1; CP.47; CP.34; CP.106; CP.66.leta